2011
DOI: 10.1016/j.jmb.2011.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the p53 DNA-Binding Domain with Its N-Terminal Extension Modulates the Stability of the p53 Tetramer

Abstract: The tetrameric tumor suppressor p53 plays a pivotal role in the control of the cell cycle and provides a paradigm for an emerging class of oligomeric, multidomain proteins with structured and intrinsically disordered regions. Many of its biophysical and functional properties have been extrapolated from truncated variants, yet the exact structural and functional role of certain segments of the protein is unclear. We found from NMR and X-ray crystallography that the DNA-binding domain (DBD) of human p53, usually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 53 publications
3
91
0
Order By: Relevance
“…The boundaries of the p53 core domain were recently questioned by the finding that cation-π interaction of R174 and W91 stabilizes the domain (27). Methyl NMR spectra of the N-terminally extended core domain (89-296) spectra are significantly different from the shorter 94-296 construct (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The boundaries of the p53 core domain were recently questioned by the finding that cation-π interaction of R174 and W91 stabilizes the domain (27). Methyl NMR spectra of the N-terminally extended core domain (89-296) spectra are significantly different from the shorter 94-296 construct (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S2A) indicate that chemical exchange observed in the extended core domain is caused by an internal slow-conformational dynamics within the domain. The recent X-ray studies of an extended p53C domain (27) and the magnitudes of observed chemical shift perturbations suggest that the second set of NMR signals observed in the methyl NMR spectra results from breaking of the R174-W91 cation-π interaction, which allows the "opening" of the p53C-PRR hinge and increases the solvent exposure of W91 residue. This mechanism is corroborated by methyl NMR spectrum of a p53C (89-296) W91A mutant, which exhibits single set of cross-peaks resembling the "minor" conformation of the native p53C (89-296) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between Trp91 and Arg174 in the p53 DNA-binding domain increases the melting temperature by several degrees and decreases the rate of aggregation compared with constructs that begin just a few residues away, such as at Ser94 (Natan et al 2011). In the DNA-binding domain structure, this interaction may hold the N-terminal region in an orientation that counteracts the exposure of the aggregation-prone region (Fig.…”
Section: Mechanisms Underlying the Prion-like Aggregation Of Tumor Sumentioning
confidence: 99%
“…Although the behavior of individual domains may be modified by domain interactions in vivo, the properties of major domains within multidomain proteins frequently have a strong impact on the full-length protein. For example, the stability and levels of folded p53 in vivo are dictated by the p53CD (43,44) with additional modulation by domain interactions and phosphorylation (45,46). In this work, we present the first report on the conformational stability and folding of the RbAB pocket domain, which presents the main interaction sites with both cellular and viral proteins and is the site of most tumorigenic point mutations.…”
mentioning
confidence: 88%